Motýlí kniha - Gravensteen, A.; Bolavá, Anna, 1981-; Borkovec, Petr, 1970-; Faulerová, Lucie, 1989-; Joklová, Olga, 1985-2015; König, Jakub, 1978-; Šindelka, Marek, 1984-; Zbořil, Jonáš, 1988- (Paseka, 2020)
Zbierka poviedok, ktorú inšpirovali zápisky Olgy Joklové, statočnej ženy, ktorá trpela chorobou motýlích krídel.